Tender is the bite - Quinn, Spencer (Quinn, Spencer. Chet and Bernie mystery., 2021)
"Spencer Quinn's Tender Is the Bite is a brand new adventure in the New York Times and USA Today bestselling series that Stephen King calls "without a doubt the most original mystery series currently available." Chet and Bernie are contacted by a terribly scared young woman who seems to want their help. Before she can even tell them her name, she flees in panic. But in that brief meeting Chet sniffs out an important secret about her, a secret at the heart of the mystery he and Bernie set out to solve. It's a case with no client and no crime and yet great danger, with the duo facing a powerful politician who has a lot to lose. Their only hope lies with a ferret named Griffie who adores Bernie. Is there room for a ferret in the Chet and Bernie relationship? That's the challenge Chet faces, the biggest of his career. Hanging in the balance are the lives of two mistreated young women and the future of the whole state"--